The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3324/haematol.2020.253476
|View full text |Cite
|
Sign up to set email alerts
|

NUP98 and KMT2A: usually the bride rather than the bridesmaid

Abstract: Relapses and treatment-related events contributed equally to poor prognosis in children with ABLclass fusion positive B-cell acute lymphoblastic leukemia treated according to AIEOP-BFM protocols. Haematologica 2020;105(7): 1887-1894. 10. Schwab C, Ryan SL, Chilton L, et al. EBF1-PDGFRB fusion in pediatric B-cell precursor acute lymphoblastic leukemia (BCP-ALL): genetic profile and clinical implications. Blood. 2016;127(18):2214-2218. 11. Conter V, Bartram CR, Valsecchi MG, et al. Molecular response to treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…NUP98 rearrangement (r) is present in AML [20] and rarely in B/M MPAL with NUP98::NSD1 [ 7 , 21 ], and MLLT1 is a recurrent partner of KMT2A -r in acute leukemias . Additionally, NUP98 fusions are associated with HOX gene/protein upregulation, especially HOXA [ 22 , 23 ]. Other genetic lesions resulting in HOXA dysregulation include KMT2A -r and SET::NUP214 [ 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…NUP98 rearrangement (r) is present in AML [20] and rarely in B/M MPAL with NUP98::NSD1 [ 7 , 21 ], and MLLT1 is a recurrent partner of KMT2A -r in acute leukemias . Additionally, NUP98 fusions are associated with HOX gene/protein upregulation, especially HOXA [ 22 , 23 ]. Other genetic lesions resulting in HOXA dysregulation include KMT2A -r and SET::NUP214 [ 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NUP98::KMT2A chimera lacks the MEN1 interacting domain of KMT2A, but includes most other important KMT2A functional domains and also does not upregulate HOX genes. [20][21][22] Studies in mouse embryonal fibroblasts using an inducible NUP98::KMT2A construct suggested that this chimeric protein was able to prevent cellular senescence through a HOX gene independent mechanism and resulted in leukemogenesis only after a long latency, which could be shortened with radiation-therapy, implying that additional mutations were required to trigger tumorigenesis. 22 Similarly, sarcomas with VIM::KMT2A fusions appear to arise in older individuals, which is unusual for many fusion-associated sarcomas, and have been associated with additional mutations in CTNNB1, SMARCB1, and ARID1A, 2 which are all known cancer genes, and may be required for transformation in this entity.…”
Section: Discussionmentioning
confidence: 99%
“…The closest analogy to this fusion event is seen in a rare subset of AML with a peculiar NUP98 exon 13:: KMT2A exon 2 fusion, and studies in leukemia may shed light on the mechanism of action in sarcoma. The NUP98::KMT2A chimera lacks the MEN1 interacting domain of KMT2A , but includes most other important KMT2A functional domains and also does not upregulate HOX genes 20–22 . Studies in mouse embryonal fibroblasts using an inducible NUP98::KMT2A construct suggested that this chimeric protein was able to prevent cellular senescence through a HOX gene independent mechanism and resulted in leukemogenesis only after a long latency, which could be shortened with radiation‐therapy, implying that additional mutations were required to trigger tumorigenesis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the NUP98::HOXA9 fusion gene needs functional KMT2A for leukemogenesis [49,52,53]. In contrast, the rare NUP98::KMT2A fusion seems to unfold its leukemogenic potential through cell cycle alteration rather than through HOX gene upregulation [54,55]. Aside from the variable pathogenetic roles of different NUP98-fusions, NUP98-rearranged murine models show a huge variability in phenotypes such as myeloproliferation, myelodysplasia, and secondary or de novo leukemic transformation [56][57][58][59][60].…”
Section: Nup98::ash1l In Context Of Nup98-rearrangementsmentioning
confidence: 99%